Cooperative Tertiary Amine/Chiral Iridium Complex Catalyzed Asymmetric [4+3] and [3+3] Annulation Reactions. (11th September 2019) - Chen, Zhi‐Chao; Chen, Zhi; Yang, Zhen‐Hong; Guo, Li; Du, Wei; Chen, Ying‐Chun
Abstract: Asymmetric reactions merging organocatalysis and metal catalysis significantly broaden the scope of organic synthesis. Nevertheless, the accomplishment of stereoselective annulations combining two types of dipole species, independently generated from the activations of organocatalysts and metal complexes, still remains as a challenging task. Now, Morita–Baylis–Hillman carbonates from isatins and carbamate‐functionalized allyl carbonates could be chemoselectively activated by achiral Lewis basic tertiary amines and chiral iridium complexes. The zwitterionic allylic ylides and 1, 4‐π‐allyliridium dipoles formed in situ are assembled in a highly stereoselective [4+3] annulation pattern. Similar cooperative catalytic strategy could be applied for the reactions of Morita–Baylis–Hillman carbonates and vinyl aziridines, furnishing an asymmetric [3+3] annulation reaction also with excellent stereocontrol. Abstract : Morita‐Baylis‐Hillman‐Carbonate aus Isatinen und Carbamat‐funktionalisierten allylischen Carbonaten wurden durch ein Lewis‐basisches tertiäres Amin und einen chiralen Iridiumkomplex aktiviert. Die resultierenden zwitterionischen allylischen Ylide und im π‐Allyliridiumkomplex vorhandenen 1, 4‐Dipole vollziehen regio‐ und stereoselektive [4+3]‐Anellierungen. Äquivalente 1, 3‐Dipole aus Vinylaziridinen wurden in asymmetrischen [3+3]‐Anellierungen eingesetzt.